Talk at meetings in a Malaysian small-medium enterprise / Teoh Mei Lin - Teoh, Mei Lin (2014)
This study seeks to examine talk at management meetings at a Malaysian small medium enterprise. It uses Community of Practice (CofP) as the underpinning theory which allows data to be examined within the wider as well as the local context of talk. CofP is a concept developed from the theory of social practice (Holmes 2003), and a conversation analysis (CA) influenced methodology is used to analyse the data. The analysis and interpretation of the data is carried out based on CA interactional resources such as turn taking organization, sequence organization, repair, interruptions and the use of lexis. Koester‟s (2006) term of discursive activities is used to identify the types of talk in the data. The main data comprises audio-recorded talk at the internal meetings with managers who meet regularly to discuss matters pertaining to the running of the company. Of the five recorded meetings, detailed transcriptions of two meetings comprising 253 minutes of talk time were analysed. The findings indicate that this particular CofP has shared practices which are directed towards a common goal, that is, to get work done. The practices are related to the language forms they use and the meeting talk unveiled four types of activities: checking information, giving accounts, giving instructions and problem solving. These discursive activities are demarcated by the topic change, initiated by the Chair of the meetings. The way the talk participants use CA interactional resources is then examined to see how these resources facilitate or impede their talk to achieve that common goal. iv By doing a micro level analysis of the talk within each discursive activity, it was found that in account-giving, the use of question-answer sequences propelled the discussion along and enabled the talk participants to co-construct meaning and understanding. The Chair of the meetings, who is also the General Manager, has the prerogative to terminate the discursive activity with an evaluation, a directive, or a reprimand. In checking information and giving instructions, the talk closed with the goal achieved through question-answers sequences. In the use of pronouns, it was found that the asymmetrical relationship between the Chair and the others is most obvious: the use of the institutional “we” promotes solidarity, while the individual stance of “I” shows the power she has over them. Another interactional mechanism, repair analysis, shows the power play between the GM and her subordinates. The findings of this study may contribute to various fields of discipline which include communication studies, particularly in business and management. Pedagogically, the data provides authentic talk data which may be used as resource materials in training for business communication courses and its findings may also be used to highlight the use of language in the enactment of power within business meetings and provide awareness for practitioners in this domain. Suggestions for future research may include looking into comparative studies in other contexts such as meetings in other workplaces, and with differing CofPs.